Learning Motivation and Academic Procrastination with Mathematics Learning Outcomes - Ni Putu Indah Wahyuni; Gusti Ngurah Sastra Agustika; I Wayan Wiarta (Mimbar Ilmu, 2023)
Students’ motivation still needs to improve, causing students not to be enthusiastic about learning. This study aims to analyze the effect of learning motivation and academic procrastination on the results of learning mathematics for sixth-grade elementary school students. This type of research is correlational ex post facto research. The population of this study was all 106 students of class VI SD. The sample of this research was 86 students who were determined using a proportional random sampling technique. The data collection method used in this study uses the non-test method. Power collection methods using document recording, questionnaires, and tests. Data were analyzed using simple linear regression analysis techniques and multiple linear regression analysis techniques. The simple linear regression analysis results for testing hypotheses I and II showed a significant effect of learning motivation on the mathematics learning outcomes of class VI elementary school students with a contribution of 10.5%. Academic procrastination significantly affected mathematics learning outcomes of class VI elementary school students, contributing 53.0%. The multiple linear regression analysis results showed a significant influence on learning motivation and academic procrastination on the mathematics learning outcomes of sixth-grade elementary school students, with a contribution of 11.0%. Based on the results of the study, it can be concluded that learning motivation and academic procrastination have a significant effect on the learning outcomes of students in grade VI SD.